Active segmentation for immersive live avatar - Lee, SY; Kim, IJ; Ahn, SC; Kim, HG (INST ENGINEERING TECHNOLOGY-IET, 2004)
An improved segmentation method of the human body with optical IR-keying and image-based active illumination is presented. This approach provides effective generation of photo-realistic live avatars in an immersive display environment for tele-interaction.